Puerto Rico Health System Resilience After Hurricane Maria: Implications for Disaster Preparedness in the COVID-19 Era - Rios, Christopher C.; Ling, Emilia J.; Rivera-Gutierrez, Ralph; Gonzalez Sanchez, Juan; Merrell, Sylvia Bereknyei; Bruce, Janine; Barry, Michele; de Jesus Perez, Vinicio (Frontiers in Communication, 2021)
Background: Every year, Puerto Rico faces a hurricane season fraught with potentially catastrophic structural, emotional and health consequences. In 2017, Puerto Rico was hit by Hurricane Maria, the largest natural disaster to ever affect the island. Several studies have estimated the excess morbidity and mortality following Hurricane Maria in Puerto Rico, yet no study has comprehensively examined the underlying health system weaknesses contributing to the deleterious health outcomes. Methods: A qualitative case study was conducted to assess the ability of the UPR health system to provide patient care in response to Hurricane Maria. An established five key resilience framework and inductive analysis was used to identify factors that affected health system resilience. Thirteen Emergency Medicine Physicians, Family Medicine Physicians, and Hospital Administrators in a University of Puerto Rico (UPR) Community Hospital were interviewed as part of our study. Results: Of the five key resiliency components, three domains were notably weak with respect to UPR’s resiliency. Prior to the Hurricane, key personnel at the UPR hospital were unaware of the limited capacity of back-up generators at hospitals and were ill-prepared to transfer ICU patients to appropriate hospitals. Post Hurricane, the hospital faced self-regulation challenges when triaging the provision of Hurricane-related emergency services with delivering core health services, in particular for patients with chronic conditions. Finally, during and after the Hurricane, integration of patient care coordination between the UPR hospital ambulances, neighboring hospitals, and national and state government was suboptimal. The two remaining resiliency factors, addressing diverse needs and system adaptiveness in a time of crisis, were seen as strengths. Conclusions: Hurricane Maria exposed weaknesses in the Puerto Rican health system, notably the lack of awareness about the limited capacity of backup generators, poor patient care coordination, and interruption of medical care for patients with chronic conditions. As in other countries, the current COVID epidemic is taxing the capacity of the Puerto Rico health system, which could increase the likelihood of another health system collapse should another hurricane hit the island. Therefore, a resilience framework that can help health systems identify areas of improvement in preparation for possible natural disasters.